Fatty acid profile of Slovenian farmed rainbow trout - Polak, Tomaž (Array, 2021)
The present study was carried out to determine the fatty acid profile of rainbow trout (Oncorynchus mykiss) from three Slovenian fish farms; Zalog, Želimlje and Povodje. Fatty acids composition was determined on a gas chromatograph with a flame ionization detector (GC-FID). The results showed that farming conditions have a significant influence on the fatty acid composition of rainbow trout. The predominant saturated fatty acid (SFA) was palmitic acid, oleic acid was the main monounsaturated fatty acid (MUFA), while the eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were the main long chain n-3 polyunsaturated fatty acids (n-3 PUFA). The percentage of DHA exceeded that of EPA in all rainbow trout samples studied. The n-6/n-3 ratio ranged from 0.89 to 1.54 and the PUFA/SFA ratio was between 1.81 and 2.36. In dorsal and ventral fillet parts, the content of most fatty acids was similar, exceptions were observed for some PUFAs; arachidonic acid, EPA and DHA.